THE INFLUENCE OF TRUST AND EMPOWERMENT ON LECTURER RESILIENCE AT VOCATIONAL HIGHER EDUCATION INSTITUTION XYZ IN JAKARTA (IC-BESTS: International Conference on Business, Economics, Technology, and Social Sciences, 2026)
This study aims to analyze the influence of Trust and empowerment on the resilience of lecturers at Vocational Higher Education Institution XYZ, using a quantitative survey of 146 lecturers. Data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) to examine the relationships between variables. The results indicate that Trust has a positive and significant effect on lecturer resilience, with a T-statistic of 2.777, a p-value of 0.006, and a path coefficient of 0.184. Similarly, empowerment has a positive and significant effect on lecturer resilience, with a T-statistic of 1.976, a p-value of 0.048, and a path coefficient of 0.192. The findings further demonstrate that Trust and empowerment jointly contribute to enhancing lecturer resilience. Trust fosters psychological safety, strengthens working relationships, and boosts organizational commitment. At the same time, empowerment drives improvements in competence, autonomy, and lecturer motivation in carrying out the Three Pillars of Higher Education (*Tri Dharma Perguruan Tinggi*). The study concludes that strengthening an organizational culture grounded in Trust and empowerment is an effective strategy for enhancing lecturer resilience, thereby supporting the sustainability and competitiveness of the vocational higher education institution.